1998
DOI: 10.1021/ic970809l
|View full text |Cite
|
Sign up to set email alerts
|

A New Class of Carborane Compounds for Second-Order Nonlinear Optics:  Ab Initio Molecular Orbital Study of Hyperpolarizabilities for 1-(1‘,X‘-Dicarba-closo-dodecaborane-1‘-yl)-closo-dodecaborate Dianion (X = 2, 7, 12)

Abstract: Ab initio static electronic dipole hyperpolarizabilities, β(0), were computed for 1-(1‘,X‘-dicarba-closo-dodecaborane-1‘-yl)-closo-dodecaborane dianion (X = 2, 7, 12). These dianions have relatively large β(0) values (3.6 × 10-30 cm5 esu-1) comparable to those for 4-nitroaniline in spite of their short transition wavelengths, and the possibility for contruction of novel inorganic second-order NLO materials consisting of an electron-rich boron cluster and electron-deficient carborane cluster was presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 25 publications
0
36
0
1
Order By: Relevance
“…Moreover, the difference electron density between the ground and the first excited states was calculated as shown in Figure 3. [13] The dark-gray regions correspond to those increased electron density in the excited state, while the light-gray regions correspond to depleted regions from the ground state. Both from the MOs and the charge difference map, it is found that the benzene ring derived from DDE acts as an electrondonating group and the five-membered imide and the benzene rings derived from PMDA act as electron withdrawing groups [14], and that the first excited state is characterized by a strong intramolecular CT. [12] For the M(A-D-A) model, I ~e ADA/ of the first excited Mate (387nm light absorption) was also calculated, and it is expressed as The CI coefficients show that the predominant elctronic transition is HOMO -a LUMO and that its contribution in the first excited state is estimated to be 49%.…”
Section: Measurementsmentioning
confidence: 99%
“…Moreover, the difference electron density between the ground and the first excited states was calculated as shown in Figure 3. [13] The dark-gray regions correspond to those increased electron density in the excited state, while the light-gray regions correspond to depleted regions from the ground state. Both from the MOs and the charge difference map, it is found that the benzene ring derived from DDE acts as an electrondonating group and the five-membered imide and the benzene rings derived from PMDA act as electron withdrawing groups [14], and that the first excited state is characterized by a strong intramolecular CT. [12] For the M(A-D-A) model, I ~e ADA/ of the first excited Mate (387nm light absorption) was also calculated, and it is expressed as The CI coefficients show that the predominant elctronic transition is HOMO -a LUMO and that its contribution in the first excited state is estimated to be 49%.…”
Section: Measurementsmentioning
confidence: 99%
“…The strong bonds between carborane and metal combined with high electronic delocalization provide great stability and diverse applications of these compounds [3,7] in medicine [9][10][11][12] and materials sciences [13][14][15][16][17][18][19][20] [16]. In addition, Grüner et al [18] obtained a derivative [12-C 7 H + 6 -CB 11 H − 11 ] with β ten times larger than p-nitroaniline (9.2 × 10 −30 cm 5 /esu) [24].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in this area involving carboranes include synthesis of novel compounds [14,18] and NLO properties' calculations [5,8,[15][16][17]21,28]. For example, a new class of dodecarboranes ([B 12 H 11 -C 2 B 10 H 11 ] 2− ) with potential application as NLO materials was proposed through ab initio calculations (1)…”
mentioning
confidence: 99%
“…Calculations predict large hyperpolarizability (b) values [13] and Bernard et al demonstrated the donor potential of the B 12 cluster by linear absorption studies of cluster containing non-centrosymmetric p-conjugated systems [14], so the cluster in combination with acceptor substituents promises to be an interesting new electron donor for nonlinear optical materials. N,N,N-trialkylammonioundecahydro-closo-dodecaborates(1-) [15] represent a new type of anions for use as ionic liquids [16,17].…”
Section: Introductionmentioning
confidence: 99%